Teaching Skills for Community-Based Preceptors (Out of Print) - Leslie Sadownik (Association of American Medical Colleges, 2006)
Abstract This resource is a quick teaching reference guide for physician instructors. The content of the 42-page pocket-sized booklet addresses the educational principles and skills that physicians need to teach medical learners effectively in the ambulatory clinical setting. Topics include characteristics of effective teachers, how learners learn, time-saving tips, task-specific teaching, taking an educational history, developing an educational plan, facilitating clinical reasoning skills, and the importance of observation, feedback, and assessment of learners.